HYDROGENATION OF D-GLUCOSE TO D-MANNITOL USING RANEY NICKEL CATALYST (Journal of Engineering, 2009)
Hydrogenation of D-glucose in the presence of Raney nickel as a catalyst was employed for the preparation of D-mannitol. The effects of the reaction time (15-115 min), reaction temperature (15-65 oC), and catalyst to D-glucose ratio (3-11 %) on the yield of D-mannitol were studied. The experimental design of Box-Wilson method was adopted to find a useful relationship between the effecting variables and the D-mannitol yield. The experimental data collected by this design was successively fitted to a second order polynomial mathematical model. The analysis of variance shows that the reaction time had the greatest effect on the yield of D-mannitol among other variables. An optimum operating conditions of 115 min reaction time, 50 ˚C reaction temperature, and 3 % catalyst to D-glucose ratio gave 14.01 % D-mannitol yield, 81.34 % D-sorbitol yield, and 94.9 % D-glucose conversion. D-Mannitol of purity 99.7 % was obtained after its separation from D-sorbitol, the second product of the hydrogenation process, using the fractional crystallization method